A review: Relationship between Inhibin B level and some trace elements in female infertility - Jasim Mohammed , Rehab; Joudah Radhi , Inam; T Omran , Zena (Pure Sciences International Journal of Kerbala, 2024)
The granulosa cells of the female ovary generate the transforming growth factor (TGF-) superfamily member, inhibin B. Instead of being a possible indicator of male and female poverty, it serves as a motivator for change. As part of the utero-placental unit's paracrine ovarian and testicular regulators, it is now known to have several paracrine functions. This study investigated the relationship between inhibin B levels and a few trace components in women who were infertile.